2017
DOI: 10.1111/adb.12520
|View full text |Cite
|
Sign up to set email alerts
|

Temporally specific miRNA expression patterns in the dorsal and ventral striatum of addiction‐prone rats

Abstract: MicroRNAs (miRNAs) within the ventral and dorsal striatum have been shown to regulate addiction-relevant behaviours. However, it is unclear how cocaine experience alone can alter the expression of addiction-relevant miRNAs within striatal subregions. Further, it is not known whether differential expression of miRNAs in the striatum contributes to individual differences in addiction vulnerability. We first examined the effect of cocaine self-administration on the expression of miR-101b, miR-137, miR-212 and miR… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
30
0
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 37 publications
(31 citation statements)
references
References 49 publications
(88 reference statements)
0
30
0
1
Order By: Relevance
“…These new set points and relative sensitization of specific brain circuits could contribute epigenetically to increased risk for MHD. In rodent models of stress, obesogenic diet, and substance misuse (methamphetamine, cocaine, and opioids), miRNA levels have been shown to be dynamically regulated in the ventral basal ganglia, and in the methamphetamine model, corresponded to specific shared miRNA levels in circulating serum exosomes [64][65][66][67][68].…”
Section: Potential Environmental Factors For Intergenerational and Trmentioning
confidence: 99%
“…These new set points and relative sensitization of specific brain circuits could contribute epigenetically to increased risk for MHD. In rodent models of stress, obesogenic diet, and substance misuse (methamphetamine, cocaine, and opioids), miRNA levels have been shown to be dynamically regulated in the ventral basal ganglia, and in the methamphetamine model, corresponded to specific shared miRNA levels in circulating serum exosomes [64][65][66][67][68].…”
Section: Potential Environmental Factors For Intergenerational and Trmentioning
confidence: 99%
“…Indeed, differences between structures in the reward system of obese and nonobese humans or rodents have been described, and it was suggested that obese individuals share behavioral and neurobiological similarities with those addicted to drugs . When examining rats after chronic exposure to cocaine, two populations can be identified—those that are prone to develop addiction and those that are resistant (some mouse models of addiction also reveal populations that differ in their motivation to obtain the reward, but these are not yet established for cocaine). In previous studies, others and we found that obesity‐prone rats show behavioral and neural properties similar to those of cocaine‐exposed rats .…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, overexpression of this gene in NAc attenuates cocaine-induced place preference in mice 51 . On the other hand, miR-137 and miR-101 are down-regulated in the NAc of cocaine self-administrated rats compared to controls 52 . This is the first time that miR-9-5p, miR-369-3p and miR-153-3p are found down-regulated after cocaine treatment.…”
Section: Discussionmentioning
confidence: 82%